Penggunaan Metode AHP dan GIS Untuk Zonasi Daerah Rawan Banjir Rob di Wilayah Medan Utara - Saputra, Novrizal Ardian; Tarigan, A. Perwira Mulia; Nusa, Ahmad Bima (Department of Civil Engineering, Diponegoro University, 2020)
Tidal floods that occur in the North Medan area due to overflowing of sea water when the tide enters the land, both directly and through river floods. The land area affected by tidal floods is getting wider and wider, so there needs to be an analysis of the level of vulnerability of tidal flooding so that the handling and prevention efforts can be on target. Determination of zonation with the level of tidal flood hazard involves various criteria, for this reason the AHP and GIS integration method is used to make rational decisions from several criteria and draw them on a zoning map. The results obtained in the North Medan area showed that 30.91 ha (0.33%) had very high levels, 1,515.98 ha (16.09%) had high levels, 4,411.92 ha (46.83%) had moderate levels, 3,176.83 ha (33.72%) had low levels, 284.81 ha (3.02%) had very low levels of vulnerability to tidal flooding.